Effects of 174 G/C polymorphism in the promoter region of the interleukin-6 gene on plasma IL-6 levels and muscle strength in elderly women - Pereira,D.S. (2011)
We investigated the effect of -174 G/C single-nucleotide polymorphism in the promoter region of the IL6 gene on plasma IL-6 levels and muscle strength, and the relationship between IL-6 levels and muscle strength in elderly women. The sample consisted of 199 elderly residents (73.0 ± 7.8 years old) from rest homes and the community in Belo Horizonte, MG, Brazil. -174 G/C polymorphism was determined by direct sequencing of the product by PCR, and plasma IL-6 concentrations were measured by ELISA. Muscle strength in the knee joint was evaluated using a Biodex System 3 Pro® isokinetic dynamometer. ANCOVA was used to determine the effect of polymorphism on IL-6 levels and muscle strength, and the Pearson correlation coefficient to assess the relationship between IL-6 levels and muscle strength. -174 G/C polymorphism was associated with the plasma IL-6 levels of elderly women (P < 0.01) since homozygotes for the G allele showed high IL-6 levels (GG 3.85 pg/mL, GC + CC 2.13 pg/mL). There was no association of polymorphism on muscle strength (P > 0.05). No association was found between IL-6 levels and knee extensor muscle (r = 0.087, P = 0.306) or flexor (r = -0.011, P = 0.894) strength. An interaction between -174 G/C polymorphism and housing conditions of the sample of elderly women was identified, with the effect of genotype on IL-6 levels being higher in the institutionalized elderly. These results support the evidence that -174 G/C polymorphism of the IL6 gene associates with individual variability of plasma IL-6 levels in elderly women.